The New Basel accord: Some potential implications of the new standards for credit risk - Esa Jokivuolle; Karlo Kauko (Bank of Finland, 2001)
This paper discusses some potential implications - both intended and unintended - of The New Basel Accord, which is to be finalized by the end of 2001.Our focus is on the reforms of the rules for determining minimum capital requirements for credit risk.The discussion is divided into effects at the level of an individual bank, effects on the structure of the financial markets, and macroeconomic implications.We present a survey of potential effects rather than a profound analysis of any of them.Therefore conclusions are inevitably preliminary, and in many cases they are likely to be controversial.Although the new capital accord as a whole is a major improvement on many properties of the current framework, our aim is to find potential problems that might need to be considered in the implementation and application of the new rules.Overall, the new accord will be largely an experiment, of which many of the consequences remain to be seen.
URN:NBN:fi:bof-20140807488
Keywords: 330; The New Basel Accord; capital adequacy requirements; credit crisk; banking stability